Cooled radiofrequency ablation provides extended clinical utility in the management of knee osteoarthritis: 12-month results from a prospective, multi-center, randomized, cross-over trial comparing cooled radiofrequency ablation to a single hyaluronic acid injection - Chen, Antonia F.; Khalouf, Fred; Zora, Keith; DePalma, Michael; Kohan, Lynn; Guirguis, Maged; Beall, Douglas; Loudermilk, Eric; Pingree, Matthew J.; Badiola, Ignacio; Lyman, Jeffrey (BMC musculoskeletal disorders, 2020)
Safe and effective non-surgical treatments are an important part of the knee osteoarthritis (OA) treatment algorithm. Cooled radiofrequency ablation (CRFA) and hyaluronic acid (HA) injections are two commonly used modalities to manage symptoms associated with knee OA. A prospective 1:1 randomized study was conducted in 177 patients comparing CRFA to HA injection with follow-ups at 1, 3, 6 and 12 months. HA subjects with unsatisfactory outcomes at 6-months were allowed to crossover and receive CRFA. Knee pain (numeric rating scale = NRS), WOMAC Index (pain, stiffness and physical function), overall quality of life (global perceived effect = GPE, EQ-5D-5 L), and adverse events were measured. At 12-months, 65.2% of subjects in the CRFA cohort reported ≥50% pain relief from baseline. Mean NRS pain score was 2.8 ± 2.4 at 12 months (baseline 6.9 ± 0.8). Subjects in the CRFA cohort saw a 46.2% improvement in total WOMAC score at the 12-month timepoint. 64.5% of subjects in the crossover cohort reported ≥50% pain relief from baseline, with a mean NRS pain score of 3.0 ± 2.4 at 12 months (baseline 7.0 ± 1.0). After receiving CRFA, subjects in the crossover cohort had a 27.5% improvement in total WOMAC score. All subjects receiving CRFA reported significant improvement in quality of life. There were no serious adverse events related to either procedure and overall adverse event profiles were similar. A majority of subjects treated with CRFA demonstrated sustained knee pain relief for at least 12-months. Additionally, CRFA provided significant pain relief for HA subjects who crossed over 6 months after treatment. This trial was registered on ClinicalTrials.gov, NCT03381248. Registered 27 December 2017.